Optimalisasi Keuntungan Industri Kecil Kerupuk Ikan Gabus Di Desa Kota Raden Hulu Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara - Arief Hidayatullah; Titi Hidayati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
This study aims to determine the optimal benefits of small fish chips cork industry with limited available resources and perform sensitivity analysis on the optimal conditions For small industry profits cork fish crackers. Methods of data collection through census method. The data is taken from interviews with all members of the population. The population of small cork fish cracker industry is the one that cultivates both types (large packaged cork crackers and small cork fish crackers) as many as 15 small industries of cork fish crackers in Kota Raden Hulu Village, all of which were respondents in this study.. Based on a linear programming graphical method, showed that the optimal benefit small industries crackers catfish production occurs when a large parcel cork fish crackers (X1) 299.9373 as fish crackers cork wrap and a small parcel (X2) of 643.459 packs. While the number of optimal advantage of the production is Rp. 5,727,621, -. The sensitivity analysis is known objective function coefficient limits the maximum and minimum for C1 and C2 as follows: The maximum limit for C1 (9.213,32 ≤ C1 ≤ 9.213,34), the minimum threshold for C2 (4.606,66 ≤ C2 ≤ 18.426,68). Analysis of resources and constraints shadow value indicates the function 1 has a shadow value of Rp. 57825.5.